2022
DOI: 10.3389/fneur.2022.963587
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of retinal ganglion cells in subjects with a history of repeated traumatic brain injury

Abstract: This study tested whether repeated traumatic brain injuries (TBIs) alter the objective structure or the objective function of retinal ganglion cells (RGCs) in human subjects recruited from an optometry clinic. Case subjects (n = 25) with a history of repeated TBIs (4.12 ± 2.76 TBIs over 0–41 years) and healthy pair-matched control subjects (n = 30) were prospectively recruited. Retinal nerve fiber layer (RNFL) thickness was quantified with spectral-domain optical coherence tomography, and scanning laser polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…The work reported here is part of a larger project that sought to characterize retinal structure and function in participants with a history of multiple traumatic brain injuries. Some of the results of this larger study already have been reported ( 16 ).…”
Section: Methodssupporting
confidence: 57%
See 2 more Smart Citations
“…The work reported here is part of a larger project that sought to characterize retinal structure and function in participants with a history of multiple traumatic brain injuries. Some of the results of this larger study already have been reported ( 16 ).…”
Section: Methodssupporting
confidence: 57%
“…Details about the study participants, including comprehensive TBIs histories, are reported in a companion study ( 16 ). Briefly, twenty-five ( n = 25) case participants [mean ± standard deviation (SD) age = 32.2 ± 11.8 years; 52% female; 100% White] enrolled in the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of injury first arises in the axonal head and by disorganization of the cytoskeleton and transport mechanisms, this in turn deteriorates the axon and the soma of the affected cell through a Ca2+ and calpain-induced process [53]. Even now, it is still a matter of debate if the surviving GCs will be able to maintain normal visual function in a long term [52, 54, 55], thus further studies are required in the future in this subject.…”
Section: Discussionmentioning
confidence: 99%
“…This type of injury first arises in the axonal head and by disorganization of the cytoskeleton and transport mechanisms, this in turn deteriorates the axon and the soma of the affected cell through a Ca2 + and calpain-induced process [44]. Even now, it is still a matter of debate if the surviving GCs will be able to maintain normal visual function in a long term [44,46,47], thus further studies are required in the future in this subject.…”
Section: Caspase3 Activation Cell Death Markermentioning
confidence: 99%